Rehabilitasi dan Collaborative Governance dalam Pemulihan Ekonomi Pasca Banjir Kabupaten Pidie Jaya - Zuliaden Jayus; Heri Fajri (Jurnal Ragam Pengabdian, 2026)
Flooding in Pidie Jaya Regency has had significant impacts on the social and economic conditions of the community. Damage to infrastructure, disruption of trade activities, declining business productivity, and reduced household income have become major challenges in the post-disaster recovery process. In this context, rehabilitation focuses not only on physical reconstruction but also on restoring community economic activities through the involvement of multiple stakeholders. This study aims to analyze the implementation of rehabilitation programs and the role of collaborative governance in supporting post-flood economic recovery in Pidie Jaya Regency. The research employed a qualitative method with a descriptive approach. Data were collected through in-depth interviews, field observations, and documentation studies involving local government officials, business actors, community organizations, and flood-affected residents. The findings indicate that economic rehabilitation was carried out through the restoration of economic infrastructure, the distribution of social and economic assistance, and the strengthening of community business capacities. Collaborative governance was reflected in the cooperation among local government, the private sector, community organizations, and local communities in planning, implementing, and evaluating recovery programs. Such collaboration accelerated economic recovery and enhanced public participation. However, challenges remain, including limited resources, suboptimal coordination among stakeholders, and issues related to program sustainability. Therefore, stronger synergy and collective commitment are essential to achieving a more effective, inclusive, and sustainable economic recovery.